Design of a NodeMCU-Based Real-Time Air Quality Monitoring System Using the Blynk Application - Wirawan, Elvan Satria; Asni Tafrikhatin; Instianti Elyana (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
Currently, air quality monitoring is only through satellites, so this monitor is only general; even though sometimes we need an air quality monitor to measure air quality in the room or gas emissions in motor vehicles and factories, this research uses an MQ135 sensor to measure CO2 gas emissions, a DHT11 sensor to measure humidity and a NodeMCU ESP8266 microcontroller as the central brain. The system is designed to provide accurate and efficient air quality monitoring through the Internet of Things (IoT). They are integrating Blynk as a mobile device monitoring application that offers easy access to real-time air quality data. The Blynk interface allows users to monitor air conditions easily, receive notifications, and access data history. Based on the experimental results and the accuracy of the integrated temperature measurement, the system provides a reliable solution for comprehensive air quality monitoring in various environments.